Arsenic sulfide induces miR-4665-3p to inhibit gastric cancer cell invasion and migration - Zhang X; Tan Z; Kang T; Zhu C; Chen S (Dove Medical Press, 2019)
Xiuli Zhang,* Zhen Tan,* Ting Kang, Chuanying Zhu, Siyu ChenDepartment of Oncology, Xin Hua Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of ChinaCorrespondence: Siyu ChenDepartment of Oncology, Xin Hua Hospital, School of Medicine, Shanghai Jiao Tong University, 1665 Kongjiang Road, Shanghai 200092, People’s Republic of ChinaTel +86 21 2507 7642Email siyu.chen@shsmu.edu.cn*These authors contributed equally to this workPurpose: Gastric carcinogenesis is a multistep process and is the second-highest cause of cancer death worldwide with a high incidence of invasion and metastasis. MicroRNAs (miRNAs) engage in complex interactions with the machinery that controls the transcriptome and concurrently target multiple mRNAs. Recent evidence has shown that miRNAs are involved in the cancer progression, including promoting cell-cycle, conferring resistance to apoptosis, and enhancing invasiveness and metastasis. Here, we aim to elucidate the roles of miRNAs, especially microRNA-4665-3p (miR-4665-3p), in the inhibitory effect of arsenic sulfide in gastric cancer (GC).Methods: The arsenic sulfide-induced miRNA expression alterations in AGS cells was determined by miRNA microarray. RT-PCR was used to further verify the arsenic sulfide-regulated miRNAs in GC tissues. The inhibition of miR-4665-3p on the migration and invasion of GC cells were determined by wound healing assay and transwell assay. Western blot analysis was used to detect the expression of EMT related proteins and the putative target of miR-4665-3p.Results: The miR-4665-3p was up-regulated by arsenic sulfide and showed inhibition upon the migration and invasion of GC cells. MiRBase and Western blotting indicated that miR-4665-3p directly down-regulated the oncoprotein GSE1. Morphological observation also indicated that the up-regulation of miR-4665-3p inhibits the EMT in GC cells.Conclusion: Our data demonstrates that the increased expression of miR-4665-3p induced by arsenic sulfide suppresses the cell invasion, metastasis and EMT of GC cells, and has the potential to be a novel therapeutic target in GC.Keywords: arsenic sulfide, miR-4665-3p, gastric cancer, invasion, migration